Arabs in Turkish Political Cartoons, 1876-1950 : National Self and Non-National Other - Büke Okyar, İlkim (Book collections on Project MUSE., 2023)
"Büke Okyar examines the development of Turkish national identity from the 1908 constitutional revolution to the inclusion of Alexandretta in 1939, using the lens of contemporary political cartoons. The book challenges the notion that ethno-religious stereotypes of the Arab are limited to the western dichotomy of the Other and seeks to highlight the importance of previously neglected colloquial Turkish sources"--